De Novo Inverted Duplication Deletion of 4p in a 14-Week-Old Male Fetus Aborted Due to Multiple Anomalies - Fontana, Paolo; Bernardini, Laura; Lombardi, Cinzia; Giuffrida, Maria Grazia; Ciavarella, Maria; Capalbo, Anna; Maioli, Marianna; Scarano, Francesca; Cantalupo, Giuseppina; Falco, Mariateresa; Scarano, Gioacchino; Lonardo, Fortunato (Journal of Pediatric Genetics, 2020)
Inverted duplications deletions are rare, complex, and nonrecurrent chromosomal rearrangements associated with a variable phenotype. In this case report, we described the phenotype and genotype of a 14-week-old male fetus, who was aborted after discovery of multiple anomalies (septal cystic hygroma, open abdominal wall, and a nonidentifiable lower limb). At autopsy, fluorescence in situ hybridization and array comparative genomic hybridization identified an inverted duplication with terminal deletion of 4p [46,XY,der(4)del(p16.3)dup(4)(p15.2p16.3)]. Only five genotypically similar cases have been reported, and we hope our case contribution will add meaningful to the body of knowledge.
Keywords: inv dup del; 4p; gastroschisis; agenesis; lung hypoplasia